MacIntyre's "after virtue" at 40 - Angier, Tom 1970- (Cambridge University Press, 2024)
"Since its publication in 1981, Alasdair MacIntyre's After Virtue has made a significant impact throughout the humanities disciplines. This new collection unpacks the influence of After Virtue on ethical and political theory, sociology and theology, and offers a multi-faceted exploration of its significance"--
Keywords: MacIntyre, Alasdair C. -- 1929- -- After virtue; MacIntyre, Alasdair C. / After virtue; MacIntyre, Alasdair C. / Criticism and interpretation; Virtue; Ethics; Vertus; Morale; ethics (philosophy); MacIntyre, Alasdair C.; After virtue (MacIntyre, Alasdair C.); Criticism, interpretation, etc; Aufsatzsammlung